2008
DOI: 10.1292/jvms.70.513
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Abdominal Leiomyosarcoma in a Ferret (Mustela Putorius Furo): Histopathological and Immunohistochemical Characterization

Abstract: ABSTRACT. A 5 years old female ferret with an abdominal palpable mass confirmed at echo-graphic examination died during an explorative laparotomy. A single lymph-node-like nodule was found adjacent to the intestinal loops. The round mass well circumscribed, solid and white, histologically, at low magnification, appeared encapsulated and built up by a population of atypical spindle cells arranged in interwoven fascicles. The cells had high anisocytosis degree, moderate mitotic activity and prominent nucleoli. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…This raises the question, whether these tumours could have the potential to secrete hormones, leading to the described clinical signs in ferrets. Unfortunately, the primary site of the intra-abdominal tumour could not be determined and hormone levels were not stated by the authors (17).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This raises the question, whether these tumours could have the potential to secrete hormones, leading to the described clinical signs in ferrets. Unfortunately, the primary site of the intra-abdominal tumour could not be determined and hormone levels were not stated by the authors (17).…”
Section: Discussionmentioning
confidence: 96%
“…Instead, an inguinal mass representing a neoplastic cryptorchid tesicle was found. The microscopic and immunohistochemical findings, such as positive reaction for α-SMA and desmin and negative cytokeratin labeling, indicated that the neoplastic cells were of smooth muscle origin (1,7,12,17). This led to the diagnosis of a multilobular, partly infiltrating testicular leiomyosarcoma with compression of pre-existing tissue, interstitial cell hyperplasia, and marked reactive proliferation of collagen-rich fibrous tissue.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…8 Recently, another intraabdominal leiomyosarcoma was reported and probably was of intestinal origin. 11 However, KIT immunolabeling was not performed to differentiate GISTs from other mesenchymal neoplasms in these earlier reports. In human medicine, definitive diagnosis of GIST requires positive immunolabeling of tumor cells for KIT, as recommended by the National Institutes of Health (NIH) Consensus Conference.…”
mentioning
confidence: 96%
“…Only 2 of the neoplasms were of mesenchymal origin; 1 was a leiomyoma of the cecum and 1 a leiomyosarcoma of the rectum 8 . Recently, another intra-abdominal leiomyosarcoma was reported and probably was of intestinal origin 11 . However, KIT immunolabeling was not performed to differentiate GISTs from other mesenchymal neoplasms in these earlier reports.…”
mentioning
confidence: 99%